Cancer‐testis gene PIWIL1 promotes cell proliferation, migration, and invasion in lung adenocarcinoma. (23rd November 2017) - Xie, Kaipeng; Zhang, Kai; Kong, Jing; Wang, Cheng; Gu, Yayun; Liang, Cheng; Jiang, Tingting; Qin, Na; Liu, Jibin; Guo, Xuejiang; Huo, Ran; Liu, Mingxi; et al.
Abstract: Piwi‐like RNA‐mediated gene silencing 1 ( PIWIL1 ) has been identified as a novel extremely highly expressed cancer‐testis (CT) gene in lung adenocarcinoma. However, the exact function and mechanism of PIWIL1 in lung adenocarcinoma remains unclear. Herein, we sought to investigate the role of PIWIL1 in the occurrence and development of lung adenocarcinoma. We examined the expression pattern of PIWIL1 in The Cancer Genome Atlas (TCGA) lung adenocarcinoma samples, and validated it by Real‐Time PCR (RT‐PCR) in additional 21 paired lung adenocarcinoma tissues and 16 normal tissues. Subsequently, we explored the biological function of PIWIL1 in A549 and H1299 cell lines by gain and loss‐of‐function analyses. Using TCGA lung adenocarcinoma data, we further performed coexpression and Gene Ontology (GO) analyses, and analyzed the association of DNA methylation levels in PIWIL1 promoter region with its expression. Finally, we evaluated its expression in different mutation status of significantly mutated genes (SMGs) in TCGA lung adenocarcinoma data. We observed that PIWIL1 was expressed in testis and lung adenocarcinoma but not in other normal tissues, and its high expression was associated with shortened survival of lung cancer patients. Overexpression of PIWIL1 could facilitate the proliferation, invasion and migration of lung adenocarcinoma cells and vice versa. GO analysis revealed that PIWIL1 upregulated genes were enriched in embryonic development, cell proliferation and regulation of transcription. Moreover, promoter DNA hypomethylation of PIWIL1 could contribute to its aberrant expression in tumors. Interestingly, PIWIL1 expression was significantly higher in patients without hepatocyte growth factor ( HGF ) or serine/threonine kinase 11 ( STK11 ) mutation ( P = 0.006 and 0.005, respectively). PIWIL1 is an epidriver gene in lung adenocarcinoma, indicating a potential target for further therapy. Abstract : PIWIL1 is a novel extremely highly expressed cancer‐testis gene in lung adenocarcinoma. PIWIL1 could promote the ability of proliferation, invasion, and migration in lung adenocarcinoma. The expression status of PIWIL1 is regulated by methylation in promoter region.